The Representation of Education News on the Ministry of Education and Culture Website - Fitri Yuliana; Pratomo Widodo; Titik Sudartinah; Vita Diah Setyoningrum (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Every reader can get a distinctive representation from a news article. This representation can also shape readers' attitudes regarding the news that they read. This is caused by the words used in the news. The objectives of this research were to obtain a representation of the meaning of news on the Ministry of Education and Culture website and to determine the impact of that representation. The research design used in this re Background: Education is a crucial element that can drive transformative changes across various aspects of life. The motivation to enhance educational standards within society may be influenced by a range of factors, both direct and indirect, including exposure to reading materials. Analyzing the linguistic features through corpus analysis can reveal the frame of a language. The objectives of this research were to obtain a representation of the meaning of news on the Ministry of Education and Culture website and to determine the impact of that representation. Methodology: The research design used in this research was a qualitative method. The data for this research were obtained from the official Kemendikbudristekportal and examined using the AntConc application. Findings: This research discovered that one of the representations of education news contained in the official website of the Ministry of Education and Culture is that they are working to convince Indonesians to help advance education in Indonesia and to make people more aware of the importance of education. Conclusion: As a result, educational news has an advantageous impact. Originality: This research focuses on studying educational news and its impact on representation.